FORENSIC AUDIT AS AN INSTRUMENT TO DISCLOSE CORRUPTION: A CASE STUDY OF THE SEI WAMPU BRIDGE PROJECT - Aris Setiono; Andreanov; Salman Farizi; Abdizil Ikhram Lubis; Lasson Padang; Akhiril Akbar Hasibuan; Rahima Br Purba (International Journal of Management, Economic and Accounting, 2025)
Corruption in government-managed infrastructure projects remains a major problem in state financial management. This study aims to examine the function of forensic audits as an investigative tool in identifying corrupt practices, focusing on the Sei Wampu Bridge Project in Langkat Regency, North Sumatra. The methodology used is a descriptive qualitative approach based on document analysis from court decision Number 124/ Pid . Sus-TPK/2023/PN. Mdn . The research findings indicate that forensic audits have a significant role in exposing various forms of corruption, including the appointment of non-existent contractors, fraudulent contract documents, unauthorized payments, and the diversion of project funds to unauthorized parties. Forensic audits also provide solid and measurable evidence in legal proceedings, including account statements, contract documents, and reports on the physical progress of the project. This study confirms that forensic audits not only function as a tool for detection, but also as a crucial instrument in increasing accountability and transparency in public budget management.